Exploring the Effect of Exercise Physiology Intervention Among Adolescent and Young Adults Diagnosed With Cancer. Issue 2 (April 2019) - Murnane, Andrew; Thompson, Kate; Mancuso, Sam G.; Lewin, Jeremy; Orme, Lisa M.
Abstract : Background: Exercise in the adult oncology setting has proven to be an effective intervention in improving patients' physical condition and mental health and reducing treatment side effects; however, its role in the adolescent and young adult (AYA) population is less well understood. This study aimed to explore the effects of an exercise physiology (EP) intervention on the functional capacity of AYA diagnosed with malignancy. Methods: A prospective, single-institution cohort study was conducted of all AYA patients who were referred to the EP service and participated in baseline and postintervention assessment. Patients were provided with an individualized exercise program aimed at improving functional capacity as measured by the Six-Minute Walk Test, maximum push-ups, arm curls, and Sit-to-Stand Test, and a hand-held dynamometer was used to measure limb strength. Results: Fifty-one patients were included in the analysis, with predominant histological subgroups being sarcoma (37%) and lymphoma (26%). Thirty-seven percent of patients completed the program while on treatment and 63% were posttreatment. For those on treatment, there were significant improvement between baseline and postintervention strength assessments in sit-to-stand, push-ups, and arm curls, with robust effect sizes (Cohen's d R ) ranging from small ( d R = −0.02, U 3 = 49%) to large ( d R = 1.05, U 3 = 85%). For posttreatment AYA, there were differences between all baseline and postintervention functional and strength assessments, with effect sizes ranging from small ( d R = 0.30, U 3 = 61.8%) to large ( d R = 1.29, U 3 = 90.1%). Conclusion: An individualized exercise intervention had a positive effect on AYA cancer patients' physical performance both while undergoing treatment and posttreatment. Future randomized controlled trials are required to validate these findings.